2008
DOI: 10.1016/j.ymeth.2007.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Methods for kinetic and thermodynamic analysis of aminoacyl-tRNA synthetases

Abstract: The accuracy of protein synthesis relies on the ability of aminoacyl-tRNA synthetases (aaRSs) to discriminate among true and near cognate substrates. To date, analysis of aaRSs function, including identification of residues of aaRS participating in amino acid and tRNA discrimination, has largely relied on the steady state kinetic pyrophosphate exchange and aminoacylation assays. Pre-steady state kinetic studies investigating a more limited set of aaRS systems have also been undertaken to assess the energetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 93 publications
3
120
0
Order By: Relevance
“…This finding was quite puzzling, since all three homologs seemed to be properly folded as evaluated by circular dichroism spectroscopy and have dimeric structure as shown by size-exclusion chromatography. The activation of all 20 standard amino acids by the aSerRS homologs was therefore tested by a complementary method, the amino acid-depended ATP-pyrophosphate exchange assay (16). The results confirmed that only A. tumefaciens homolog is capable of serine activation, but revealed that alanine and glycine are also its substrates (Fig.…”
Section: Truncated Sers-like Genes Encode Homologs Of Methanogenic-typementioning
confidence: 74%
See 2 more Smart Citations
“…This finding was quite puzzling, since all three homologs seemed to be properly folded as evaluated by circular dichroism spectroscopy and have dimeric structure as shown by size-exclusion chromatography. The activation of all 20 standard amino acids by the aSerRS homologs was therefore tested by a complementary method, the amino acid-depended ATP-pyrophosphate exchange assay (16). The results confirmed that only A. tumefaciens homolog is capable of serine activation, but revealed that alanine and glycine are also its substrates (Fig.…”
Section: Truncated Sers-like Genes Encode Homologs Of Methanogenic-typementioning
confidence: 74%
“…ATP-PP i exchange assay was performed at 30°C in 50 mM TrisHCl pH 7.5, 150 mM KCl, 0.2 mg∕mL BSA, 4 mM DTT, 20 mM MgCl 2 , 4 mM ATP, and 1 mM ½ 32 P − PP i , and varying concentrations of amino acids. Reaction was quenched, products were separated on polyethylenimine-cellulose TLC plates and quantified by phosphorimaging (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because 2′dA-tRNA and ddA-tRNA are missing the functional 2′ hydroxyl group that is necessary for aminoacylation to occur, AMP formation in these reactions would reflect cycles of amino acid activation and hydrolysis that are representative of pretransfer editing (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was carried out at 28 1C and 5 ml time point aliquots collected. The assay was performed in triplicate and the active enzyme concentration was determined by measuring the amplitude of the burst phase of Leu-AMP formation 24,25 .…”
Section: Methodsmentioning
confidence: 99%